OLD AND NEW IN MANAGEMENT AND ACCOUNTING. - Littleton, A. C. (The Accounting Review, 1954)
Abstract In order to operate an enterprise well, management needs to plan future operations and maintain close control over materials and activities. One of the most useful techniques of planning is forward budgeting. Its figures are based on known intentions decided by high-level authority and on knowledge of the results of prior activities that grew out of prior planning. This necessary knowledge de- rives from detailed records (i.e. accounting) periodically compacted into summary reports. Of the many techniques of managerial control, several that are essential include to set up an operating organization and carefully provide for subdivided duties. It may be helpful if production standards are established as a guide to workers and supervisors. Secondly, provide trained personnel, plus suitable supervision, frequent inspection, etc. Although, present day accountants may justly take pride in the intricate techniques and the professional status of our independent auditors. Yet they can well afford now and then to acknowledge a large intellectual debt to generation after generation of unknown contributors to this art.